1994
DOI: 10.1172/jci117433
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mediated skeletal muscle vasodilation is nitric oxide dependent. A novel action of insulin to increase nitric oxide release.

Abstract: The purpose of this study was to examine whether insulin's effect to vasodilate skeletal muscle vasculature is mediated by endothelium-derived nitric oxide (EDNO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
646
2
19

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,137 publications
(703 citation statements)
references
References 38 publications
36
646
2
19
Order By: Relevance
“…Similarly, other studies have shown that endothelium-dependent vasodilation was impaired in thoracic aorta rings from rats infused with glucosamine and that this was a result of the inhibition of NOS by glucosamine [19]. Since both the insulin-mediated increases in total flow [15,36] and capillary recruitment [16] have been suggested to be NOSdependent, this could be the mechanism for the glucosamine-mediated inhibition of capillary recruitment and total flow. The effects of glucosamine on gene expression in endothelial cells [37] should also be considered, if longer-term exposure occurs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly, other studies have shown that endothelium-dependent vasodilation was impaired in thoracic aorta rings from rats infused with glucosamine and that this was a result of the inhibition of NOS by glucosamine [19]. Since both the insulin-mediated increases in total flow [15,36] and capillary recruitment [16] have been suggested to be NOSdependent, this could be the mechanism for the glucosamine-mediated inhibition of capillary recruitment and total flow. The effects of glucosamine on gene expression in endothelial cells [37] should also be considered, if longer-term exposure occurs.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence from a number of laboratories indicates that limb blood flow is controlled by insulin acting via a NO-dependent mechanism presumed to be initiated via vascular endothelial cells [15,36,39]. However, the role of limb blood flow in insulin-mediated glucose uptake is at best controversial [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, tempting to speculate that the increased stiffness found in subjects with type 2 diabetes may be due in part to insulin resistance. 41 …”
Section: Type 2 Diabetes Mellitus and Endothelial Dysfunctionmentioning
confidence: 99%
“…The acute vascular effect of insulin in healthy men is vasodilation by stimulation of nitric oxide production and secondarily by stimulation of vasodilating prostaglandins. 3,4 Early in the course of insulin-dependent diabetes mellitus (IDDM), before the occurrence of overt retinopathy, a decrease in retinal blood flow is present that correlates with plasma glucose levels. 5 In contrast, in IDDM with poor metabolic control, elevated cardiac output and forearm blood flow Correspondence: Dr PC Chang, Department of Nephrology, C3-P, Leiden University Medical Center, PO Box 9600, 2300 RC Leiden, The Netherlands Received 9 July 1998; revised and accepted 19 October 1998 vascular resistance were related to the plasma glucose concentrations both glucose infusions were equipotent.…”
Section: Introductionmentioning
confidence: 99%